Factors affecting elk (Cervus elaphus) encounter rate by gray wolves (Canis lupus) in Yellowstone National Park - Martin, Hans (2016)
University of Minnesota M.S. thesis. May 2016. Major: Natural Resources Science and Management. Advisor: L. David Mech. 1 computer file (PDF); viii, 71 pages. Few studies of wolf predation have quantified wolf encounter rates of prey and the factors that influence them. Elk population decline, variable weather, and changing wolf-pack dynamics on the Northern Range (NR) of Yellowstone National Park (YNP) provide an opportunity to examine factors affecting wolf-elk encounter rates and their role in wolf hunting success. Wolf kill rate is influenced by several factors but not by elk density. However, I found that elk density seems to be the only factor that drives wolf-elk encounter rates, and encounter rates are somewhat correlated with hunting success at least during early winter. Thus the factors affecting wolf hunting success of elk on the NR of YNP do not explain variation in encounter rates. Wolves appear to be able to adjust their hunting behavior to compensate for all the factors predicted to affect encounter rates except for elk density.